Analisis Kualitas Layanan Perdagangan Umum pada PT Varia Usaha Fabrikasi - Ummu Lisa’ada; Moh. Agung Surianto; Tiara Khoerunnisa; Prayudi Harianto (Economic Reviews Journal, 2024)
This research aims to analyze the quality of general trading services at PT. Varia Fabrication Business and to determine the influence of service quality through aspects (Tangibility, Reliability, Responsiveness, Guarantee, Empathy) on customer satisfaction. This research uses a qualitative descriptive approach, and uses data collection techniques in the form of in-depth interviews. The results of this research show that the tangible aspect is said to be very good in accordance with customer demand with quality products at affordable prices. In terms of vendor reliability, it is not good because of the limited time given by the user to the vendor, resulting in delays in sending price quote requests. In the aspect of responsiveness, it is very well known from the statements of informants who are quite satisfied with the products and try to receive complaints from customers. From the guarantee aspect, it is very good, apart from quality products, we are also satisfied with PT. Varia Fabrication Business because the delivery of goods is accompanied by a goods guarantee letter. In terms of attention, it is very good that communication goes well, is easy to contact and is always polite and friendly to customers. From the conclusions, the author provides several suggestions, namely evaluating performance with the concept of being on time, preferably PT. Varia Usaha Fabricasi carries out performance evaluations, where management must eliminate all forms of activities that do not have added value, then PT. Varia Fabrication Business needs to be committed to improving quality, continuously improving services and simplifying activities so that operational activities are more effective